Pengaruh Pendidikan Kesehatan Terhadap Perubahan Tingkat Pengetahuan Dan Sikap Petani Tentang Penggunaan Alat Pelindung Diri (APD) DI Desa Pangkalan Karangrayung Grobogan - WIBOWO, EKO AGUS, Abi Muhlisin, SKM, M.Kep, Sri Enawati, S.K p , M.Kes (2016)
Farmer is a job of informal sector and people who work in informal sector are usually having lesser knowledge about importance of personal protective equipment than those who work in formal sector. Availability and the use of personal protective equipment are also different. In formal jobs such as industry, personal protective equipment is provided by companies and it is supervised by certain parties such as Labor Office so that occupational health and safety in formal sector is more secured. While farmers with their limited conditions are usually using simple personal protective equipment, so their occupational health and safety is very not secured as in formal sector. Purpose of the Research: Purpose of the research is to know effect of health education on change of knowledge level and attitude of farmers about the use of personal protective equipment in Pangkalan Village, Karangrayung, Grobogan. Method: The research is experimental one with pretest-posttest control group design. Population of the research was 406 farmers of Pangkalan Village, Karangrayung, Grobogan. Sample was taken by purposive random sampling, namely 40 farmers or 10% of 406 individuals who were suitable with inclusion criteria. Data of the research was examined by using univariate and bivariate statistical tests. Results of the research effect of health education by using leaflet and power point media on knowledge indicates that the value t = 4,773 and  = 0,0001. Results of the research effect of health education by using leaflet and power point media on attitudes indicates that the value t = 9,140 and  = 0,0001. Change of knowledge level and attitude of farmers was found to be higher in treatment group after provision of health education about the use of personal protective equipment. Effect of health education by using leaflet and power point media was found on knowledge level and attitude of farmers about the use of personal protective equipment in Pangkalan Village, Karangrayung, Grobogan.